Informing fitness testing data reporting and visualization in elite soccer: a survey into practitioner preferences and needs - Asimakidis, N. D.; Beato, M.; Parmar, N.; Weldon, A.; Bishop, C.; Turner, A. N. (The Journal of Strength and Conditioning Research, 2026)
This cross-sectional survey explored elite soccer practitioners' fitness testing reporting and visualization preferences. Overall, 145 soccer practitioners completed an online survey comprising 27 questions, with 3 sections: (a) background information, (b) preferences for fitness testing report content and insights, and (c) preferences and interpretation of data visualization formats. Fixed-response questions were analyzed using frequency analysis, while thematic analysis was applied to open-ended questions to generate key themes. Subjects predominantly valued tracking changes (91%) in performance over benchmark (61%) or position-specific (58%) comparisons. Although 44.8% prioritized individual performance, 42.1% emphasized both individual and team-level insights. Concerning the presentation of data, raw scores were the preferred format (62.1%), followed by standardized (37.2%) and composite scores (23.5%), depending on the context. Subjects highly valued interactive dashboards (91%), quadrant charts (87.6%), and traffic light systems (77.2%). Bar charts (77.2%) were the preferred visual format for interplayer comparisons, valued for their clarity, and reduced cognitive load, while line charts (51.7%) were favored for tracking performance over time, due to their simplicity and user familiarity. Radar charts (59.3%) were the preferred format for comparing individual performances to the wider team, valued for their ability to provide a holistic overview of strengths and weaknesses. Uncertainty indicators were endorsed by 52.3%, primarily for enhancing data interpretation and decision making, although concerns were raised about their ease of understanding and visual clutter. Practitioners can use this study's findings to inform user-friendly reporting strategies and meet diverse audience needs. Findings should also support practitioner training and the adoption of evolving industry practices.